Parathyroid Hormone in Pregnancy: Vitamin D and Other Determinants - Hysaj, Ola (Nutrients, 2021)
We aimed to assess the parathyroid hormone (PTH) concentration in pregnant women at the beginning of pregnancy (1st trimester) and within days before delivery (3rd trimester) and evaluate its determinants. From September 2014 through December 2015 in a cross-sectional study, 204 women in the 1st trimester of pregnancy and 203 women in the 3rd trimester of pregnancy were recruited. Blood samples were collected to measure PTH and circulating 25-hydroxy-vitamin D (25(OH)D) concentrations. Lifestyle and demographic data were collected using a questionnaire. Serum 25(OH)D and PTH were inversely correlated in both early and late pregnancy. Our analyses suggest that in the 3rd trimester of pregnancy, a 25(OH)D level of 18.9 ng/mL (47.3 nmol/L) could serve as an inflection point for the maximal suppression of PTH. Statistically significant determinants of PTH concentrations in multiple regression were 25(OH)D concentrations, season, multiparity and education of the partner (all p < 0.05) in early pregnancy. In late pregnancy, 25(OH)D concentrations and country of origin were statistically significant determinants of PTH concentrations (all p < 0.05). These factors and their effect on PTH appear to be vastly determined by 25(OH)D; however, they might also affect PTH through other mechanisms besides 25(OH)D.